Effects of the interrelationship of porcine somatotropin administration and dietary phosphorus on growth performance in developing gilts - Weeden, T.L.; Hansen, J.A.; Friesen, K.G.; Richert, B.T.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-two gilts (initial weight = 127 lb) were used to determine effects of the interrelationship of porcine somatotropin (pST) administration and dietary phosphorus (P) on growth performance of finishing gilts (127 to 235 lb) and for a 35 d postfinishing phase following withdrawal of pST administration. Gilts were injected daily with placebo (control) or 4 mg pST and fed .4, .6, or .8% P in the fmishing phase. Administration of pST increased average daily gain (ADG), improved feed efficiency (FIG), and decreased average daily feed intake (ADFI) during the finishing phase. Increasing dietary P resulted in increased ADG from d 0 to 28 of the finishing phase; however, dietary P had no effect on ADG, FIG, or ADFI for the overall finishing phase. When each block weight averaged 235 lb, half of the gilts were slaughtered. Administration of pST decreased backfat thickness, dressing percentage, and kidney fat weight and increased longissimus muscle area and carcass length. Dietary P had no effect on carcass criteria measured. The remaining 36 gilts were individually fed 4 Ibid of a common diet to assure P intake of 22.8 gld for the 35 d postfinishing phase. Gilts that received pST in the finishing phase had decreased ADG and poorer feed conversion in the postfinishing phase. Dietary P level in the finishing phase had no effect on postfinishing performance. From d 0 to 28 of the finishing phase, pST-treated gilts required a diet with more than .4% P (10.3 gld P) to maximize growth performance. However, a .4% P diet (12.4 and 10.7 gld P, control and pST-treated, respectively) is adequate for growth performance during the overall finishing phase (127 to 235 lb).
Keywords: Swine; Somatotropin; Phosphorus; Performance; Gilts